The Spirit of Gusjigang Kudus in An Interdisciplinary Approach - Suwitaningsih, Sri; Umma Farida; Moch. Dhofier; Yunus Mustaqim (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
This study presents an interdisciplinary analysis of local wisdom in Kudus City, namely Gusjigang, which has an acronym of Bagus (Good), Ngaji (Reciting), and Berdagang (Trading). The aim is to analyze the spirit of Gusjigang through an interdisciplinary approach that has an impact on entrepreneurs, especially among young people. A qualitative library research approach is used, utilizing library materials in the form of books, notes, and reports of previous research results. The interdisciplinary approach emphasizes a research model that combines or integrates two or more disciplines. In relation to the spirit of Gusjigang, the Integrative-Interconnective paradigm, namely an approach that combines religious knowledge (bayani), social sciences-humanities (burhani), and spiritual-ethical knowledge (irfani), so that Gusjigang is a local wisdom rooted in the teachings of Sunan Kudus and has become a guideline for the life of the Kudus community for generations. Although born in the context of local culture, the essence of the values ​​​​it carries is universal and easily accepted by various groups. This teaching instills a spiritual dimension that encourages humans to pay attention to the balance between physical and spiritual needs. A person’s success is measured by his ability to fulfill these two aspects: spiritual needs are fulfilled through the ability to recite the Koran, while physical needs are fulfilled through independence in trading.